Staphylococcus aureus Carotenoids Modulate the Thermotropic Phase Behavior of Model Systems That Mimic Its Membrane Composition (2022)
ABSTRACT: Staphylococcus aureus (S. aureus) is a pathogenic gram-positive bacterium that normally resides in the skin and nose of the human body. It is subject to fluctuations in environmental conditions that may affect the integrity of the membrane. S. aureus produces carotenoids, which act as antioxidants. However, these carotenoids have also been implicated in modulating the biophysical properties of the membrane. Here, we investigate how carotenoids modulate the thermotropic phase behavior of model systems that mimic the phospholipid composition of S. aureus. We found that carotenoids depress the main phase transition of DMPG and CL, indicating that they strongly affect cooperativity of membrane lipids in their gel phase. In addition, carotenoids modulate the phase behavior of mixtures of DMPG and CL, indicating that they may play a role in modulation of lipid domain formation in S. aureus membranes.